Preparation method of Janus hollow fiber membrane and Janus hollow fiber membrane prepared by same
Through the double-layer film making method and chemical grafting technology, the complexity and large-scale preparation of Janus film are solved, the precise regulation and efficient separation performance of Janus film structure are achieved, and the development of its industrial application is promoted.
Patent Information
- Application Number
- CN202311064086.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-21
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-21
AI Technical Summary
The existing Janus film preparation methods are complex, difficult to achieve large-scale and continuous preparation, and difficult to regulate the membrane structure and performance, which limits its widespread use in industrial applications.
A new Janus film preparation strategy was developed using a double-layer film making method, combined with polymer blending and chemical grafting technology. The bilayer film was prepared by coextrusion method, and hydroxyl groups were used as active sites and grafted with hydrophobic monomers to achieve grafting and growth of different hydrophobic groups at specific active sites.
The precise regulation of Janus membrane structure is achieved, the preparation process is simplified, the equipment complexity is reduced, the membrane separation efficiency is improved, and the large-scale production and application of Janus membranes in industrial applications is promoted.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a Janus hollow fiber membrane and the prepared Janus hollow fiber membrane, belonging to the field of Janus membrane preparation. Background Art
[0002] Membrane separation process has been widely used as a chemical unit operation. Membrane materials are the basis and core of membrane separation technology, which directly determines the efficiency and economy of membrane separation process. The development of new separation membrane technology is of decisive significance for expanding the application field of membrane separation and improving membrane separation efficiency. In recent years, Janus membranes with asymmetric morphology or wettability on both sides of the membrane have received widespread attention. Under the synergistic effect of the differences in microstructure and surface chemical properties on both sides of the Janus membrane, it can provide an "intrinsic" driving force for the transport of gas and liquid in the membrane. This characteristic makes Janus membrane show unique advantages over traditional separation membranes in unidirectional liquid transmission, mist collection, directional oil-water separation, membrane distillation, nanofiltration, etc. Therefore, as an emerging membrane separation technology, in-depth research on Janus membranes, exploration of their separation mechanism and optimization of membrane preparation methods are of great significance for improving the efficiency of membrane separation and expanding the application range of Janus membranes.
[0003] The structure and chemical properties of Janus membranes play a decisive role in the separation performance of the membrane. According to different properties, Janus membranes are divided into three types: two layers (A layer and B layer), two layers with large thickness difference (A on B), two layers with similar thickness (AB), and one layer gradually transitioning to another layer, that is, two symmetrical properties with gradient transition in the thickness direction of the entire membrane (A to B). The chemical property differences of Janus membranes mainly include wettability differences and charge differences. The wettability difference is determined by the microstructure and chemical composition of the membrane surface and is characterized by the contact angle (θ). One side of the Janus membrane with different wettability is superphilic / liquid-philic, while the other side is superphobic / liquid-phobic. The two sides of the charged Janus membrane have positive-negative charges with opposite surface charges, which can realize the directional transport of ions. Current research mainly focuses on the preparation and application of Janus membranes with different wettability on both sides of the membrane.
[0004] Various membrane processes place different demands on the structure of Janus membranes. According to the Lapace equation,
[0005]
[0006] ΔP is the capillary force in the membrane pores, γ is the surface tension of the liquid, θ is the water contact angle on the membrane surface, and d is the pore size of the separation membrane.
[0007] From the Lapace equation, it can be seen that the capillary force in the membrane pores is related to the wettability of the membrane material with gas or water and the membrane pore size. Therefore, in most Janus processes, only the membrane pores on one side of the hydrophilic / hydrophobic layer play a separation role, and the other side only plays a supporting role. Therefore, preparing a Janus membrane with small pores on one side (separation function) and large pores on one side (support function) can effectively reduce the transmission resistance of gas and liquid in the Janus membrane. Therefore, the two layers of the ideal Janus membrane not only need to have a difference in wettability, but also a large difference in pore size. Therefore, different membrane separation processes have specific requirements for the structure and chemical properties of the Janus membrane, which makes the preparation of the Janus membrane more difficult.
[0008] Different from the pore size screening mechanism of traditional separation membranes, Janus membranes separate by the difference in wettability on both sides of the membrane, so the preparation method of Janus membranes is more complicated. The preparation methods of Janus membranes are divided into two types: asymmetric preparation and asymmetric modification. Asymmetric preparation is the simplest method for making Janus membranes. Each layer of the membrane is prepared separately, and then the two layers of membranes are combined. Asymmetric modification is to fix the membrane in some way at the interface of two phases or the surface of one phase, and then selectively modify it on one side or both sides. From the above introduction, it can be found that the structure of the membrane, the thickness of the hydrophilic / hydrophobic layer and the transition mode have an important influence on the performance of the Janus membrane. Compared with the traditional separation membrane preparation technology, the preparation process of Janus membrane is cumbersome, the equipment is complex, the membrane structure is difficult to control, and it is difficult to achieve large-scale and continuous preparation. This is also the key factor that Janus membranes are mostly theoretical research and difficult to apply on a large scale. Therefore, developing a Janus membrane preparation method with simple process, continuous operation and universality is of great significance to promote the theoretical research and industrial application of Janus membrane separation process.
[0009] The non-solvent induced phase separation method (NIPS method) utilizes the exchange of solvent and non-solvent to form polymer-rich phase and polymer-poor phase, thereby completing the preparation process of separation membrane. The NIPS method has simple equipment and process, easy operation, and has been successfully applied to the research and production process of commercial separation membranes. The NIPS method requires the preparation of a membrane-making solution with stable properties (polymer concentration and hydrophilicity and hydrophobicity). The surface segregation process has limited control over the membrane structure and performance, making it unsuitable for use alone in the preparation process of Janus membranes with large differences in pore size, hydrophilicity / hydrophobicity, and thickness of the two layers.
[0010] Since the 1970s, flat and hollow fiber double-layer membranes prepared by double-layer scraping and co-extrusion technology have developed rapidly. The double-layer membrane is a composite of two membrane-making solutions with different properties into a nascent flat membrane and a hollow fiber membrane, and a two-layer composite structure is obtained by a one-step non-solvent induced phase separation method. The double-layer membrane preparation technology has the advantages of simple membrane preparation means, independent preparation of two-layer membrane preparation solutions, and retention of the properties of the two-layer membrane materials. It is an ideal technical means for preparing Janus membranes. However, the peeling problem between the two layers of membrane is a bottleneck restricting its application. Summary of the invention
[0011] In order to solve the above problems, this patent uses a double-layer membrane preparation method, combined with polymer blending and chemical grafting technology to develop a new Janus membrane preparation strategy. The double-layer membrane technology is used to prepare the primary ecological membrane, and the inner and outer layers contain hydrophilic amphiphilic polymers. One of them is an amphiphilic polymer with no reactive activity, and the other is an amphiphilic polymer containing active hydroxyl groups. The double-layer membrane is prepared by co-extrusion, and the distribution state of the amphiphilic polymer containing hydroxyl groups in the double-layer membrane is controlled. Then, the hydroxyl groups are used as active sites for grafting with hydrophobic monomers containing silanol groups. The chemical grafting modification technology realizes the grafting and growth of different hydrophilic / hydrophobic groups on specific active sites, thereby achieving the purpose of Janus membrane preparation.
[0012] Functional groups with similar hydrophilicity and hydrophobicity but different chemical reactivity are selected to prepare the double-layer membrane forming solution, and the distribution of the functional groups (hydroxyl groups) in the membrane thickness direction is regulated. Then, the grafting modification technology is used to realize the grafting of different hydrophilic / hydrophobic groups on the hydroxyl groups, thereby achieving the purpose of Janus membrane preparation.
[0013] The present invention first synthesizes two amphiphilic polymers (one of which contains hydroxyl groups), dissolves the two amphiphilic polymers in the inner and outer film-making solutions, and prepares a double-layer membrane by co-extrusion. Since both the inner and outer film-making solutions are hydrophilic, the two will not peel off. The resulting double-layer membrane is immersed in a grafting modification solution containing a hydrophobic monomer that reacts with hydroxyl groups, thereby converting the layer containing hydroxyl groups from hydrophilic to hydrophobic, thereby forming a Janus hollow fiber membrane.
[0014] According to one aspect of the present application, a method for preparing a Janus hollow fiber membrane is provided, comprising the following steps:
[0015] The inner layer membrane-making liquid and the outer layer membrane-making liquid are introduced into the spinning core liquid by using a double-channel nozzle, and co-extruded to obtain a double-layer hollow fiber membrane, and the modified monomer is grafted to obtain the Janus hollow fiber membrane;
[0016] The inner layer film-making solution contains a film-forming polymer A, an inner layer additive, an organic solvent A and an amphiphilic polymer A;
[0017] The outer layer film-making solution contains a film-forming polymer B, an outer layer additive, an organic solvent B and an amphiphilic polymer B;
[0018] The amphiphilic polymer A and the amphiphilic polymer B are independently selected from amphiphilic polymer I and amphiphilic polymer II;
[0019] The amphiphilic polymer contains a hydrophilic structure and a hydrophobic structure. One of the amphiphilic polymers contains a hydroxyl group and a hydrophobic group, and is named as amphiphilic polymer I. The other amphiphilic polymer is named as amphiphilic polymer II. The amphiphilic polymer is synthesized by free radical polymerization, and a hydrophilic monomer and a hydrophobic monomer are selected, and the monomer contains an olefin structure.
[0020] The amphiphilic polymer I is obtained by polymerizing a hydrophilic monomer I and a hydrophobic monomer I;
[0021] The amphiphilic polymer II is obtained by polymerizing a hydrophilic monomer II and a hydrophobic monomer II;
[0022] The hydrophilic monomer I is selected from an olefin monomer containing a hydroxyl group, specifically selected from at least one of allyl alcohol and butenol;
[0023] The hydrophilic monomer II is selected from at least one of polyethylene glycol acrylate and vinyl pyrrolidone;
[0024] The hydrophobic monomer I and the hydrophobic monomer II are independently selected from at least one of styrene, methyl acrylate, acrylonitrile and hexafluorobutyl acrylate;
[0025] The amphiphilic polymer A in the inner layer film-forming solution and the amphiphilic polymer B in the outer layer film-forming solution are different from each other;
[0026] The modified monomer is selected from at least one of hexafluorohexyltriethoxysilane and tridecafluorooctyltriethoxysilane.
[0027] The film-forming polymer A and the film-forming polymer B are independently selected from at least one of polysulfone, polyethersulfone, polyvinylidene fluoride, polymethyl methacrylate, polyvinyl chloride and polyacrylonitrile;
[0028] The inner layer additive is selected from at least one of polyethylene glycol, anhydrous lithium chloride and polyvinyl pyrrolidone;
[0029] The outer layer additive is selected from at least one of polyethylene glycol, anhydrous lithium chloride and polyvinyl pyrrolidone;
[0030] The organic solvent A and the organic solvent B are independently selected from at least one of dimethylacetamide, dimethylformamide, N-methylpyrrolidone and tetrahydrofuran;
[0031] The mass concentration of the film-forming polymer A in the inner layer film-forming solution is 10-25wt%, the mass concentration of the inner layer additive is 5-20wt%, and the mass concentration of the amphiphilic polymer A is 1-20wt%;
[0032] Optionally, the mass concentration of the film-forming polymer A in the inner film-forming solution is any value selected from 10wt%, 15wt%, 20wt%, 25wt%, or a range between any two of them; the mass concentration of the inner layer additive is any value selected from 5wt%, 10wt%, 15wt%, 20wt%, or a range between any two of them; and the mass concentration of the amphiphilic polymer A is any value selected from 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, or a range between any two of them;
[0033] The mass concentration of the film-forming polymer B in the outer layer film-forming solution is 10-25 wt %, the mass concentration of the outer layer additive is 5-20 wt %, and the mass concentration of the amphiphilic polymer B is 1-20 wt %.
[0034] Optionally, the mass concentration of the film-forming polymer B in the outer layer film-forming solution is any value among 10wt%, 15wt%, 20wt%, 25wt%, or a range between any two of them; the mass concentration of the outer layer additive is any value among 5wt%, 10wt%, 15wt%, 20wt%, or a range between any two of them; and the mass concentration of the amphiphilic polymer B is any value among 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, or a range between any two of them;
[0035] The polymerization temperature is 50 to 80°C;
[0036] Optionally, the polymerization temperature is any value of 50°C, 60°C, 70°C, 80°C, or any range between the two;
[0037] The polymerization time is 40 to 600 minutes;
[0038] Optionally, the polymerization time is any value of 40 min, 600 min, or any range between the two.
[0039] The polymerization is carried out in the presence of a catalyst;
[0040] The catalyst is selected from at least one of azobisisobutyronitrile and benzoyl peroxide.
[0041] The grafting modification monomer comprises the following steps:
[0042] immersing the double-layer hollow fiber membrane in a solvent solution containing a modified monomer;
[0043] The solvent is selected from at least one of n-hexane, cyclohexane, n-heptane, toluene, ethylbenzene and ethyl acetate;
[0044] In the solvent solution containing the modified monomer, the mass ratio of the modified monomer to the solvent is 0.01 to 0.15:1.
[0045] Optionally, in the solvent solution containing the modified monomer, the mass ratio of the modified monomer to the solvent is any value among 0.01:1, 0.05:1, 0.15:1, or a range value between any two of them.
[0046] The inner layer film-making liquid is stirred I;
[0047] The stirring temperature is 10-120°C;
[0048] Optionally, the stirring temperature I is any value of 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, or any range between two values.
[0049] The stirring time I is 1 to 20 hours.
[0050] Optionally, the stirring time I is any value among 1h, 5h, 10h, 15h, 20h, or a range value between any two of them.
[0051] The outer film-making liquid is stirred II;
[0052] The stirring temperature of II is 10 to 120° C.
[0053] Optionally, the stirring temperature II is any value of 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, or any range between two of them.
[0054] The stirring time II is 1 to 20 hours.
[0055] Optionally, the stirring time II is any value among 1h, 5h, 10h, 15h, 20h, or a range value between any two of them.
[0056] The spinning core liquid is selected from water or an aqueous solution containing ethanol, methanol, or an organic solvent;
[0057] The mass concentration of the aqueous solution containing ethanol, methanol or an organic solvent is 10-80 wt %.
[0058] The total extrusion rate of the inner film-forming liquid and the outer film-forming liquid is 3 to 20 mL / min;
[0059] Optionally, the total extrusion volume of the inner film-forming liquid and the outer film-forming liquid is any value among 3 mL / min, 5 mL / min, 10 mL / min, 15 mL / min, 20 mL / min, or a range value between any two of them.
[0060] The ratio of the extrusion amount of the inner layer film-forming liquid to the extrusion amount of the outer layer film-forming liquid is 0.1 to 10:1.
[0061] Optionally, the ratio of the extrusion amount of the inner film-forming liquid to the outer film-forming liquid is any value among 0.1:1, 0.5:1, 1:1, 5:1, 10:1, or a range value between any two of them.
[0062] The double-layer hollow fiber membrane is gel-formed;
[0063] The solution used for gel forming is selected from water or an aqueous solution containing ethanol, methanol, or an organic solvent.
[0064] The mass concentration of the aqueous solution containing ethanol, methanol or an organic solvent is 10-80 wt %.
[0065] The Janus hollow fiber membrane is washed, solvent exchanged, and dried;
[0066] The washing is water washing;
[0067] The solvent exchange is performed using ethanol and n-hexane as solvents;
[0068] The drying method is natural air drying or ethanol-n-hexane replacement air drying.
[0069] By changing the composition, flow rate, core liquid and gel bath composition of the inner and outer membrane-making liquids, Janus hollow fiber membranes with different hydrophilic / hydrophobic layer thicknesses, hydrophilicity and hydrophobicity, and pore structures can be prepared.
[0070] According to another aspect of the present application, a Janus hollow fiber membrane is provided, which is prepared by the above-mentioned preparation method.
[0071] According to another aspect of the present application, there is provided an application of the Janus hollow fiber membrane for CO 2 In the processes of absorption, flotation, ammonia nitrogen stripping and gas-liquid reaction.
[0072] The beneficial effects of this application include:
[0073] 1) The preparation method provided in the present application uses a dual-channel nozzle to prepare a double-layer separation membrane, which can flexibly adjust the thickness of the hydrophilic layer and the hydrophobic layer, the transition mode and the structure of the hydrophilic and hydrophobic layers, and realize the precise regulation of the Janus membrane structure.
[0074] 2) The preparation method provided in this application uses two membrane-forming liquids with similar hydrophilicity to prepare a double-layer membrane, which can effectively suppress the peeling problem between the two layers. In the post-processing stage, the different chemical properties of the amphiphilic polymers in the two membrane-forming liquids are utilized to experiment with the hydrophilic-hydrophobic conversion of the Janus membrane through a simple immersion grafting process.
[0075] 3) The preparation method provided in this application is easy to operate, can flexibly control the structure of the Janus membrane, and is more conducive to the large-scale production and industrial application of Janus hollow fiber membranes.
[0076] 4) The Janus separation membrane developed in this application can be used in processes such as flotation, ammonia nitrogen stripping and gas-liquid reaction, which can greatly enhance gas-liquid mass transfer and reduce equipment investment and operating costs. DETAILED DESCRIPTION
[0077] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0078] Unless otherwise specified, the raw materials and hydrophobic monomers in the examples of the present application were purchased through commercial channels.
[0079] Example 1
[0080] Take 8g of acryl alcohol and 2g of styrene, dissolve them in 415g of dimethylacetamide, add 0.1g of azobisisobutyronitrile, introduce nitrogen, heat and stir at 50°C for 40min to obtain a solution containing amphiphilic polymer I. Add 50g of PVDF and 25g of polyethylene glycol 400 to this solution to obtain an inner layer membrane solution.
[0081] Take 20g of vinyl pyrrolidone and 5g of styrene, dissolve them in 350g of dimethylacetamide, add 0.5g of azobisisobutyronitrile, heat and stir at 60℃ for 80min to obtain a solution containing amphiphilic polymer II. Add 100g of PVDF and 25g of polyethylene glycol 400 to this solution to obtain an outer layer film-making solution.
[0082] The inner film-making liquid and the outer film-making liquid are added to the inner film-making liquid spinning tank and the outer film-making liquid spinning tank respectively, and vacuum degassing is carried out for 24 hours. The outer film-making liquid and the inner film-making liquid are respectively injected into the double-channel nozzle, and ethanol is used as the core liquid and deionized water is used as the outer gel bath to spin a double-layer hollow fiber membrane. The flow rate of the outer film-making liquid is 5ml / min, and the inner film-making liquid is 0.5ml / min to obtain a double-layer hollow fiber membrane. The obtained double-layer hollow fiber membrane is immersed in the grafting modification solution, and the grafting reaction is carried out for 24 hours. The composition of the grafting modification solution is 1g of hexafluorohexyltriethoxysilane and 100g of n-hexane. The grafted double-layer membrane is rinsed in deionized water for 48 hours, and ethanol-n-hexane is replaced and dried successively to obtain a Janus hollow fiber membrane. The Janus membrane has a hydrophobic inner layer and a hydrophilic outer layer structure. The inner water contact angle is 125° and the outer water contact angle is 38°.
[0083] The separation membrane was used to absorb CO by bubbling method. 2 process.
[0084] Take N 2 / CO 2 Mixed gas (N 2 85%, CO 2 The mixed gas is pressurized into the Janus membrane module from the air inlet of the Janus membrane module, flows into the Janus hollow fiber membrane from the outer surface of the Janus hollow fiber membrane and combines with the absorbent to form microbubbles. The pressure of the mixed gas is 0.15MPa, and the pressure of the absorbent is 0.02MPa. The microbubbles combine with the absorbent inside the membrane module and in the subsequent absorption tube, and the gas-liquid separation is achieved through the gas-liquid separator. The gas after absorption enters the gas chromatograph to test the CO in the mixed gas. 2 content.
[0085] The test results are as follows: the average diameter of the microbubbles in the mixed gas is 30μm, and the processing volume of the mixed gas is 7m 3 / m 2 h, CO in the mixed gas after absorption 2 The absorption rate is 99.97%, which can operate stably for a long time.
[0086] Example 2
[0087] Take 30g of butenol and 10g of methyl methacrylate, dissolve them in 350g of dimethylacetamide, add 0.1g of azobisisobutyronitrile, introduce nitrogen, heat and stir at 70°C for 200min to obtain a solution containing amphiphilic polymer I. Add 100g of polyethersulfone and 20g of anhydrous lithium chloride to this solution to obtain an outer layer film-forming solution.
[0088] Take 40g of polyethylene glycol acrylate and 10g of methyl acrylate, dissolve them in 360g of dimethylacetamide, add 0.5g of azobisisobutyronitrile, and heat and stir the mixture at 60°C for 400min to obtain a solution containing amphiphilic polymer II. Add 70g of polyethersulfone and 20g of anhydrous lithium chloride to the solution to obtain an inner layer film-forming solution.
[0089] The inner film-making liquid and the outer film-making liquid are added to the inner film-making liquid spinning tank and the outer film-making liquid spinning tank respectively, and vacuum degassing is carried out for 24 hours. The outer film-making liquid and the inner film-making liquid are respectively injected into the double-channel nozzle, and water is used as the core liquid and propanol is used as the outer gel bath to spin a double-layer hollow fiber membrane. The flow rate of the outer film-making liquid is 1.5ml / min, and the inner film-making liquid is 3.5ml / min to obtain a double-layer hollow fiber membrane. The obtained double-layer hollow fiber membrane is immersed in the grafting modification solution, and the grafting reaction is 24h. The composition of the grafting modification solution is 5g hexafluorohexyltriethoxysilane and 95g toluene. The grafted double-layer membrane is rinsed in deionized water for 48h, and ethanol-n-hexane is replaced and dried successively to obtain a Janus hollow fiber membrane. The Janus membrane has a hydrophobic outer layer and a hydrophilic inner layer structure. The inner layer water contact is 25°, and the outer layer water contact angle is 130°.
[0090] The separation membrane was used in the direct contact membrane distillation process, and the test water source was saline water with a salt content of 3.5% and a water temperature of 80°C. The saline water flowed through the outer hydrophobic layer of the Janus membrane, and the water vapor flowed through the inner hydrophilic layer of the Janus separation membrane, and desalted water was obtained after condensation.
[0091] Water output is 80L / m 2 h, the desalination rate reaches 99.8%.
[0092] Example 3
[0093] 45 g of butenol and 15 g of methyl methacrylate were dissolved in 350 g of dimethylformamide, 0.3 g of benzoyl peroxide was added, nitrogen was introduced, and the mixture was heated and stirred at 80°C for 500 min to obtain a solution containing amphiphilic polymer I. 80 g of polyvinyl chloride and 10 g of polyvinyl pyrrolidone were added to the solution to obtain an outer layer film-forming solution.
[0094] Take 60g of vinyl pyrrolidone and 15g of hexafluorobutyl acrylate, dissolve them in 330g of dimethylformamide, add 0.4g of benzoyl peroxide, heat and stir at 90°C for 600min to obtain a solution containing amphiphilic polymer II. Add 75g of polyvinyl chloride and 20g of polyvinyl pyrrolidone to this solution to obtain an inner layer film-making solution.
[0095] The inner film-making liquid and the outer film-making liquid are added to the inner film-making liquid spinning tank and the outer film-making liquid spinning tank respectively, and vacuum degassing is carried out for 24 hours. The outer film-making liquid and the inner film-making liquid are respectively injected into the double-channel nozzle, and a 70% DMAC / 30% deionized water mixture is used as the core liquid, and deionized water is used as the outer gel bath to spin a double-layer hollow fiber membrane. The flow rate of the outer film-making liquid is 3ml / min, and the flow rate of the inner film-making liquid is 7ml / min to obtain a double-layer hollow fiber membrane. The obtained double-layer hollow fiber membrane is immersed in the grafting modification solution, and the grafting reaction is carried out for 24 hours. The composition of the grafting modification solution is 10g hexafluorohexyltriethoxysilane and 90g n-hexane. The grafted double-layer membrane is rinsed in deionized water for 48 hours, and ethanol-n-hexane is replaced and dried successively to obtain a Janus hollow fiber membrane. The Janus membrane has a hydrophobic outer layer and a hydrophilic inner layer structure. The inner water contact angle is 35° and the outer water contact angle is 135°.
[0096] The separation membrane was used in the direct contact membrane distillation process, and the test water source was saline water with a salt content of 3.5% and a water temperature of 80°C. The saline water flowed through the outer hydrophobic layer of the Janus membrane, and the water vapor flowed through the inner hydrophilic layer of the Janus separation membrane, and desalted water was obtained after condensation.
[0097] Water output is 60L / m 2 h, the desalination rate reaches 99.8%.
[0098] Comparative Example 1:
[0099] Take 60g of vinyl pyrrolidone and 15g of hexafluorobutyl acrylate, dissolve them in 330g of dimethylformamide, add 0.4g of benzoyl peroxide, heat and stir at 90°C for 600min to obtain a solution containing amphiphilic polymer. Add 75g of polyvinyl chloride and 20g of polyvinyl pyrrolidone to this solution to obtain a membrane-forming solution.
[0100] The membrane solution was added to the spinning tank and vacuum degassed for 24 hours. The membrane solution was injected into a single-channel nozzle, and a 70% DMAC / 30% deionized water mixture was used as the core liquid and deionized water was used as the outer gel bath to spin a double-layer hollow fiber membrane. The membrane solution flow rate was 3 ml / min, and a hydrophilic PVDF hollow fiber membrane was obtained with a water contact angle of 35°.
[0101] Take N 2 / CO 2 Mixed gas (N 2 85%, CO 2The mixed gas is pressurized into the membrane assembly from the air inlet of the PVDF separation membrane assembly, flows into the hollow fiber membrane from the outer surface of the PVDF membrane and combines with the absorbent to form microbubbles. The pressure of the mixed gas is 0.15MPa, and the pressure of the absorbent is 0.04MPa. The microbubbles combine with the absorbent inside the membrane assembly and in the subsequent absorption tube, and the gas-liquid separation is achieved through the gas-liquid separator. The gas after absorption enters the gas chromatograph to test the CO in the mixed gas. 2 content.
[0102] After the test, the gas flux approached zero within 30 minutes and could not be operated.
[0103] Comparative Example 2:
[0104] Take 40g of allyl alcohol and 10g of methyl acrylate, dissolve them in 360g of dimethylacetamide, add 0.5g of azobisisobutyronitrile, heat and stir at 60°C for 400min to obtain a solution containing amphiphilic polymer. Add 70g of polyethersulfone and 20g of anhydrous lithium chloride to this solution to obtain an inner film-making solution. Add the film-making solution to the spinning tank and vacuum degas for 24h. Pour the film-making solution into a single-channel nozzle, use water as the core liquid and propanol as the outer gel bath to spin a hollow fiber membrane. The membrane-making liquid is 3.5ml / min to obtain a hollow fiber membrane. Soak the prepared hollow fiber membrane in a grafting modification solution for 24h of grafting reaction. The composition of the grafting modification solution is 10g of hexafluorohexyltriethoxysilane and 90g of n-hexane. The grafted double-layer membrane was rinsed in deionized water for 48 h, and then replaced and dried with ethanol-n-hexane successively to obtain a hydrophobic hollow fiber membrane with a water contact angle of 135°.
[0105] The separation membrane was used in the direct contact membrane distillation process, and the test water source was saline water with a salt content of 3.5% and a water temperature of 80°C. The saline water flowed through the outer hydrophobic layer of the Janus membrane, and the water vapor flowed through the inner hydrophilic layer of the Janus separation membrane, and desalted water was obtained after condensation.
[0106] Water output is 20L / m 2 h, the desalination rate reaches 99.8%.
[0107] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a Janus hollow fiber membrane, characterized in that: The following steps are involved: The inner layer membrane-making liquid and the outer layer membrane-making liquid are introduced into the spinning core liquid by using a double-channel nozzle, and co-extruded to obtain a double-layer hollow fiber membrane, and the modified monomer is grafted to obtain the Janus hollow fiber membrane; The inner layer film-making solution contains a film-forming polymer A, an inner layer additive, an organic solvent A and an amphiphilic polymer A; The outer layer film-making solution contains a film-forming polymer B, an outer layer additive, an organic solvent B and an amphiphilic polymer B; The amphiphilic polymer A and the amphiphilic polymer B are independently selected from amphiphilic polymer I and amphiphilic polymer II; The amphiphilic polymer I is obtained by polymerizing a hydrophilic monomer I and a hydrophobic monomer I; The amphiphilic polymer II is obtained by polymerizing a hydrophilic monomer II and a hydrophobic monomer II; The hydrophilic monomer I is selected from at least one of allyl alcohol and butenol; The hydrophilic monomer II is selected from at least one of polyethylene glycol acrylate and vinyl pyrrolidone; The hydrophobic monomer I and the hydrophobic monomer II are independently selected from at least one of styrene, methyl acrylate, acrylonitrile and hexafluorobutyl acrylate; The amphiphilic polymer A in the inner layer film-forming solution and the amphiphilic polymer B in the outer layer film-forming solution are different from each other; The modified monomer is selected from at least one of hexafluorohexyltriethoxysilane and tridecafluorooctyltriethoxysilane.
2. The preparation method according to claim 1, characterized in that: The film-forming polymer A and the film-forming polymer B are independently selected from at least one of polysulfone, polyethersulfone, polyvinylidene fluoride, polymethyl methacrylate, polyvinyl chloride and polyacrylonitrile; The inner layer additive is selected from at least one of polyethylene glycol, anhydrous lithium chloride and polyvinyl pyrrolidone; The outer layer additive is selected from at least one of polyethylene glycol, anhydrous lithium chloride and polyvinyl pyrrolidone; The organic solvent A and the organic solvent B are independently selected from at least one of dimethylacetamide, dimethylformamide, N-methylpyrrolidone and tetrahydrofuran; The mass concentration of the film-forming polymer A in the inner layer film-forming solution is 10-25wt%, the mass concentration of the inner layer additive is 5-20wt%, and the mass concentration of the amphiphilic polymer A is 1-20wt%; The mass concentration of the film-forming polymer B in the outer layer film-forming solution is 10-25 wt %, the mass concentration of the outer layer additive is 5-20 wt %, and the mass concentration of the amphiphilic polymer B is 1-20 wt %.
3. The preparation method according to claim 1, characterized in that: The polymerization temperature is 50 to 80°C; The polymerization time is 40 to 600 minutes; The polymerization is carried out in the presence of a catalyst; The catalyst is selected from at least one of azobisisobutyronitrile and benzoyl peroxide.
4. The preparation method according to claim 1, characterized in that: The grafting modification monomer comprises the following steps: immersing the double-layer hollow fiber membrane in a solvent solution containing a modified monomer; The solvent is selected from at least one of n-hexane, cyclohexane, n-heptane, toluene, ethylbenzene and ethyl acetate; In the solvent solution containing the modified monomer, the mass ratio of the modified monomer to the solvent is 0.01 to 0.15:
1.
5. The preparation method according to claim 1, characterized in that: The inner layer film-making liquid is stirred I; The stirring temperature is 10-120°C; The stirring time I is 1 to 20 hours.
6. The preparation method according to claim 1, characterized in that: The outer film-making liquid is stirred II; The stirring temperature of II is 10 to 120° C. The stirring time II is 1 to 20 hours.
7. The preparation method according to claim 1, characterized in that: The spinning core liquid is selected from water or an aqueous solution containing ethanol, methanol, or an organic solvent; The mass concentration of the aqueous solution containing ethanol, methanol or an organic solvent is 10-80 wt %.
8. The preparation method according to claim 1, characterized in that: The total extrusion rate of the inner film-forming liquid and the outer film-forming liquid is 3 to 20 mL / min; The ratio of the extrusion amount of the inner layer film-forming liquid to the extrusion amount of the outer layer film-forming liquid is 0.1 to 10:
1.
9. A Janus hollow fiber membrane, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
10. An application of the Janus hollow fiber membrane according to claim 9, characterized in that: Used in CO2 absorption, flotation, ammonia nitrogen stripping and gas-liquid reaction processes.
Citation Information
Patent Citations
Preparation method of hollow-fiber asymmetric composite membrane
CN103657437A
Novel Janus polymer hollow fiber membrane and preparation method and application thereof
CN109621734A
Janus polytetrafluoroethylene hollow fiber membrane and preparation method thereof
CN110394068A
Membrane casting solution, preparation method thereof and application of membrane casting solution in preparation of Janus hollow fiber membrane
CN115957634A
Hollow fiber membrane
EP2567750A1